2014
DOI: 10.1038/jcbfm.2014.58
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Measurements of Brain Tissue Pulsatility Correlate with the Volume of MRI White-Matter Hyperintensity

Abstract: White-matter hyperintensity (WMH) is frequently seen in magnetic resonance imaging (MRI), but the complete physiopathology of WMH remains to be elucidated. In this study, we sought to determine whether there is an association between the maximum brain tissue displacement (maxBTD), as assessed by ultrasound, and the WMH, as observed by MRI. Nine healthy women aged 60 to 85 years underwent ultrasound and MRI assessments. We found a significant negative correlation between maxBTD and WMH (ρ=-0.86, P<0.001), sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 15 publications
2
35
0
Order By: Relevance
“…It was shown that BTP was increased during visual stimulation (Kucewicz et al, 2007) and was decreased during hyperventilation (Kucewicz et al, 2008), which suggests that BTP is closely related to CBF changes and cerebrovascular reactivity (CVR), consistently with the notion that pulsatile CBF and cerebrovascular functioning are major determinants of brain pulsatility (Wagshul et al, 2011). Our team also found that TPI was informative in clinical settings, as BTP was shown to be inversely correlated with WMH load (Ternifi et al, 2014). In another pilot study (Desmidt et al, 2011), we investigated the use of TPI in LLD, and we found that BTP was markedly lower in diabetic depressed patients compared with diabetic non-depressed subjects.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…It was shown that BTP was increased during visual stimulation (Kucewicz et al, 2007) and was decreased during hyperventilation (Kucewicz et al, 2008), which suggests that BTP is closely related to CBF changes and cerebrovascular reactivity (CVR), consistently with the notion that pulsatile CBF and cerebrovascular functioning are major determinants of brain pulsatility (Wagshul et al, 2011). Our team also found that TPI was informative in clinical settings, as BTP was shown to be inversely correlated with WMH load (Ternifi et al, 2014). In another pilot study (Desmidt et al, 2011), we investigated the use of TPI in LLD, and we found that BTP was markedly lower in diabetic depressed patients compared with diabetic non-depressed subjects.…”
Section: Introductionsupporting
confidence: 74%
“…Based on previous results on LLD and CVDs, we hypothesized that BTP would be lower in depressed patients compared with controls and remitted subjects. We also compared BTP with WMHs and CBF in the middle cerebral artery (MCA), as assessed by TCD and MRI arterial spin labeling (ASL), as potential cofounders of BTP (Ternifi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence indicating that the severity of symptoms is directly correlated with the serum or CSF concentration of anti-NMDAR antibodies 5. Although many patients with anti-NMDAR encephalitis have areas of hyperintensity on brain MRIs, this finding is non-specific and can be seen in many other central nervous system disorders 6. Most patients with anti-NMDAR encephalitis have abnormal EEG findings, and around 30% of them will demonstrate extreme delta brush waves on EEG which is very specific for this disease 7.…”
Section: Discussionmentioning
confidence: 99%
“…The small displacements of brain areas can be estimated using backscattered ultrasound (US) signals and tissue Doppler signal processing methods for a radiofrequency (RF) US. This allows the investigation of endogenous displacements of brain areas excited by respiratory and cardiac activity [1,2,[5][6][7]. The popular version of this method was developed by Kucewicz et al [2,5] and called tissue pulsatility imaging (TPI).…”
Section: Introductionmentioning
confidence: 99%
“…The popular version of this method was developed by Kucewicz et al [2,5] and called tissue pulsatility imaging (TPI). Brain tissue pulsatility measured by TPI is closely related to changes in cerebral blood flow [2,5,6]. The most recent research [8][9][10] deals with the development of quantitative shear wave-based passive elastography.…”
Section: Introductionmentioning
confidence: 99%